Stop-Chop versus Retro-Chop Nucleotomy During Phacoemulsification. (1st November 2016) - Hwang, Ho Sik; Lee, Jee Hye; Jeon, Soo Ji; Lee, Bo Young; Cho, Yang Kyung
ABSTRACT: Purpose : To compare the outcomes of two nuclear fracture techniques used in phacoemulsification (stop-chop vs. retro-chop). Methods : A total of 131 eyes from 111 patients with severe cataracts and nucleosclerosis (of grades 4–5) were included. The patients were randomly assigned to undergo stop-chop or retro-chop nucleotomy during phacoemulsification. The Drysdale manipulator was used as the chopping instrument in both groups. The intraocular phacoemulsification parameters including phacoemulsification power and phacoemulsification time were compared across the two groups. The following parameters were compared postoperatively at 1, 2, 5, and 8 weeks using unpaired t test: corrected distance visual acuity (CDVA), corneal endothelial cell density (CD), central corneal thickness (CT). Results : There were significant differences in the phacoemulsification parameters between the groups. Retro-chop group showed less phacoemulsification time ( p < 0.05) and less phacoemulsification power ( p < 0.05) than stop-chop group. There was also a significant difference in the rate of corneal endothelial cell loss between the two groups ( p < 0.05). In contrast, there were no significant differences in the postoperative change of CT or CDVA between the groups. Conclusion : Retro-chop nucleotomy with a Drysdale nucleus manipulator is an effective and safe method. It reduces both the use of intraoperative ultrasound energy, and early postoperative corneal endothelial cell loss compared to other nucleotomy techniques.